The application towards improving notice of meeting under Nigerian company law - Shamsuddeen, Magaji; Yaacob, Nurli; Mohamed Yusoff, Zuryati (Future Academy, 2018)
The right of the shareholders to participate at the AGM depends on proper service of notice of meeting. The Companies and Allied Matters Act 1990 (CAMA 1990) recognises this right and stipulates time frame within which shareholders shall receive notice as well as the method of serving notice. However, many shareholders in Nigeria claimed that they do not receive notice of meeting on time because personal service and service through postal delivery are weak and therefore hinders their participation at AGM. This study seeks to examine the legal provisions regulating notice of AGM in Nigeria. The study adopts socio-legal and doctrinal research methodology. Accordingly, references were made to relevant statutory provisions and case law in the United Kingdom and Malaysia while qualitative interview complement the doctrinal aspect. The findings reveal that service of notice by post is not effective. There is need for the CAMA 1990 to incorporate certain provisions that will recognise the application of ICT in corporate meetings. This will improve shareholders’ participation at the AGM when notices are effectively served.